2022
DOI: 10.3389/fnagi.2022.1001241
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal association between possible new sarcopenia and the depression trajectory of individuals and their intimate partners

Abstract: BackgroundIt is currently unknown whether the dynamic nature of depression affects the development of sarcopenia. Herein, this study aims to assess the association between possible new sarcopenia and the depression trajectory of individuals and their intimate partners through a 4-year longitudinal cohort study.MethodsOur study included 784 pairs of individuals without possible sarcopenia and their spouses from the China Health and Retirement Longitudinal Study (CHARLS) 2011. All individuals and their spouses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…Our study findings indicate an increased risk of sarcopenia associated with depression, with higher CESD-10 scores being correlated with lower reported ASM values. This is consistent with existing cross-sectional evidence on the correlation between depression and sarcopenia and its components, despite the use of different measures to assess depression ( 35 , 49 53 ). In an early observational study by Yanagita et al ( 54 ), which included 2,856 Japanese-American men aged 71−93 years, depressed individuals showed a significant decline in gait speed compared to the healthy population.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study findings indicate an increased risk of sarcopenia associated with depression, with higher CESD-10 scores being correlated with lower reported ASM values. This is consistent with existing cross-sectional evidence on the correlation between depression and sarcopenia and its components, despite the use of different measures to assess depression ( 35 , 49 53 ). In an early observational study by Yanagita et al ( 54 ), which included 2,856 Japanese-American men aged 71−93 years, depressed individuals showed a significant decline in gait speed compared to the healthy population.…”
Section: Discussionsupporting
confidence: 90%
“…Based on previous studies, we collected several potential confounding variables to adjust for the association between depression and skeletal muscle mass ( 4 , 35 ). These variables include individual sociodemographic characteristics and health-related factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study also revealed that the CES-D has adequate reliability and validity for assessing depression in middle-aged and elderly Chinese community-dwelling individuals [ 21 ]. A total CES-D score ≥ 12 was regarded as indicative of depression according to previous studies [ 21 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, one predefined subgroup analysis stratified by age (≥ 60 or < 60 years) was performed to determine whether age could affect the relationship between the dynamic nature and risk of LUTS/BPH according to a previous study [ 28 ]. We completed all the statistical analyses via Empower (R) software ( www.empowerstats.com ; X&Y Solutions, Inc., Boston, MA, USA) [ 24 , 26 ]. Relative risks (RRs) with 95% CIs were used to represent the strength of all analyses, and a two-tailed p < 0.05 was considered to indicate statistical significance.…”
Section: Methodsmentioning
confidence: 99%